How does accelerometry-measured arm elevation at work influence prospective risk of long-term sickness absence? - Nidhi Gupta; Charlotte Lund Rasmussen; Mikael Forsman; Karen Søgaard; Andreas Holtermann (Nordic Association of Occupational Safety and Health (NOROSH), 2022)
OBJECTIVE: Elevated arm work is prevalent in many jobs. Feasible device-based methods are available to measure elevated arm work. However, we lack knowledge on the association between device-measured elevated arm work and prospective risk of long-term sickness absence (LTSA). We aimed to investigate this association. METHODS: At baseline, 937 workers wore accelerometers on the right arm and thigh over 1-5 workdays to measure work time spent with elevated arms in an upright position. Between baseline and 4-year prospective follow-up in the national registers, we obtained information on the individuals` first event of LTSA (≥6 consecutive weeks). We performed compositional Cox proportional hazard analyses to model the association between work time with arm elevation >30˚, >60˚, or >90˚ and the probability of LTSA. RESULTS: Workers spent 21% of their work time with >30˚ arm elevation, 4% with >60˚ arm elevation, and 1% with >90˚ arm elevation; in the upright body position. We found a positive dose-response association between work time spent with elevated arm work and the risk of LTSA. Specifically, we found that increasing two minutes of work time spent with arm elevation at (i) >90˚ increased the risk of LTSA by 14% [hazard ratio (HR) 1.14, 95% confidence intervals (95% CI 1.04-1.25)] (ii) >60˚ increased the LTSA risk by 3% (HR 1.03, 95% CI 1.03-1.06), and (iii) >30˚ increased the LTSA risk by 1% (HR 1.01, 95% CI 1.00-1.02). CONCLUSION: Device-measured elevated arm work is associated with increased prospective LTSA. This information ought to be brought into preventive workplace practice by accessible and feasible device-based methods of elevated arm work.